Da greve dos petroleiros de 1995 à greve dos eletricitários de 2018: uma análise crítica da jurisprudência dominante a respeito de greves com finalidade política - Valentim, Gabriel Lima (2021)
Every strike has a political content. The present study aims to carry out a critical analysis of the majority jurisprudential position regarding the strike for political purposes. The strike is an extremely important tool at the disposal of workers to speak out against injustices. Historically, through this institute, the proletariat fought and conquered better working conditions, higher wages and even political rights. However, in Brazil, the strike has always been resisted, some times being a criminal offense and others being accepted, but with severe restrictions. With the promulgation of the “Citizen Constitution”, the strike became a right, which was up to the workers to decide “on the interests that they should defend through”. Although the Constitution guaranteed workers a wide freedom of claim, the Superior Labor Court repeatedly declared the strike for political purposes to be abusive. However, is this restriction constitutional? Based on this central question, this work was carried out. Based on bibliographic and documentary research, with exploratory and explanatory objectives, using the hypotheticaldeductive method and case studies, elements were sought so that it could be answered. The dissertation investigates 7 strikes declared abusive by the TST, from the 1995 oil workers strike to the 2018 electricians strike. From these case studies, it is concluded that the arguments used by the Court cannot succeed. In addition to there being no legal or constitutional basis in these statements of abuse, the separations between the “politician” and the “professional” that TST commonly elaborates do not make sense in specific cases, since there are clearly professional issues involved in all the strikes analyzed. The arguments used by the Court tried to restrict the political participation of citizens to voting in the elections, a completely outdated position, which is not only at odds with the spirit of the constitution, but which is also inconsistent with what the main theorists on democracy present including liberals such as Karl Popper and John Rawls. The Court, in declaring the political strikes abusive, contributes to the separation between administration and the formation of public will, a typical phenomenon of the neoliberal era, thus contributing to the naturalization of this political project. Finally, the position of the Brazilian Court is at odds with the most modern interpretations of political strikes by the main labor courts in the West, which either accept this type of strike without great restrictions, as is the case in Italy, or accept it if there is one professional interests involved, such as France, Portugal and some judgments in Spain.